Analysis of Using Google Voice as Learning Media through Task-Based Learning Method - Indah Muzdalifah (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2021)
There are many choices of media based on Technology can be used in teaching English. One of them is Google voice, it can be found in any types of smart phone. This media can help students in recognizing the better pronunciation. Thus, it can revise their listening comprehension in English. This research is aimed to describe the role of Google voice in listening comprehension course as well as improve their listening comprehension. The method of this research is qualitative research where the data was obtained by getting the information from online questionnaire and the test. The result of this research from 43 students it was found that 91, 62% agree that the Google Voice application as the Learning English medium. Meanwhile, the result of the test after using Google voice is increasing from 68, 2% to 73, and 54%. It can be concluded that the use of Google voice gives positive effect in learning English.